Montessori Identity in Dialogue: A Selected Review of Literature on Teacher Identity - Christensen, Olivia Taylor (Journal of Montessori Research, 2019)
Montessori teacher education includes an intensive and ongoing teacher transformation. This experience aids in the development of a clearly defined teacher identity. Research on teacher identity broadly has shown that while such an identity can offer guidance and support, it can also limit teachers and prevent them from exploring other strategies that may support them and, in turn, their students (e.g., Beauchamp & Thomas, 2009; Britzman, 2003; Sumsion, 2002). This effect is problematic when teachers face moments of uncertainty and dilemmas in their teaching practice. As Montessori classrooms become increasingly diverse, teachers may need to adopt identities that are not explicitly defined in Montessori teacher transformation. This review of literature examines components of a Montessori teacher identity and, broadly, the effects of teacher identity as well as elements of antibias and antiracist teacher-identity development that includes inner reflection and an activist approach to teaching.